2015
DOI: 10.1200/jop.2015.003780
|View full text |Cite
|
Sign up to set email alerts
|

Patients and Physicians Can Discuss Costs of Cancer Treatment in the Clinic

Abstract: Purpose: As one solution to reducing costs and medical bankruptcies, experts have suggested that patients and physicians should discuss the cost of care up front. Whether these discussions are possible in an oncology setting and what their effects on the doctor-patient relationship are is not known. Methods:We used the National Comprehensive Cancer Network (NCCN) Guidelines and the eviti Advisor platform to show patients with metastatic breast, lung, or colorectal cancer the costs associated with their chemoth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
95
0

Year Published

2016
2016
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 65 publications
(96 citation statements)
references
References 24 publications
1
95
0
Order By: Relevance
“…For example, the study by Kelly et al touched on both patients’ and physicians’ attitudes toward cost communication and the associated outcomes. 17 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, the study by Kelly et al touched on both patients’ and physicians’ attitudes toward cost communication and the associated outcomes. 17 …”
Section: Resultsmentioning
confidence: 99%
“…15, 16 Over half of these studies recruited participants from cancer patients currently or previously treated in academic cancer centers or their affiliated oncology clinics. 10, 13, 14, 17-20 Three studies focused on breast cancer 10, 15, 16, 22 , one on prostate cancer 19 , and others did not focus exclusively on a specific cancer. Most studies were not restricted to a particular cancer stage, except for one that focused on metastatic cancers.…”
Section: Resultsmentioning
confidence: 99%
“…Some studies show that patients want to discuss treatment costs with their physicians, 22 and most physicians report that they frequently discuss cost with their patients. 23 However, other research has found that physicians often are hesitant about initiating cost discussions [24][25][26] and rarely fully engage with patients to resolve their financial concerns. 27 Several studies suggest that discussions of treatment costs in patient-physician clinical interactions are rare.…”
Section: Introductionmentioning
confidence: 99%
“…15, [24][25][26]28,29 Given the potential importance of cost-related discussions in cancer care, this study systematically assessed the extent and nature of actual cost discussions that occur between a sample of African American patients and their oncologists. This study focused on African Americans because, on average, African Americans are more likely than whites to have low annual household incomes 30 and, thus, may be at greater risk to incur economic hardship as a result of a cancer diagnosis.…”
Section: Introductionmentioning
confidence: 99%
“…Yet, very little harm likely results from these discussions. Kelly et al assessed patient satisfaction after the cost of chemotherapy was introduced into the doctor-patient relationship [25]. Chemotherapy and targeted-therapy costs were provided to the patient by their oncologist during the consultation, using an Internet-based decision-support platform.…”
Section: Can Cost Discussion Improve Care and Increase Value?mentioning
confidence: 99%